Pedagogical conditions of development of professional potential of future foreign language teachers in the process of their professional training - Katalin Hnatyk; Гнатик Каталін; Hnatik Katalin (Scientific Centre of Innovative Researches OÜ, 2021)
Abstract. The article under consideration gives scientific grounding of pedagogical conditions for the development of professional potential of future foreign language teachers in the process of their professional training. It has been assumed that the pedagogical conditions for the development of professional potential of future foreign language teachers in professional training should reflect: qualitative characteristics of basic factors, processes and phenomena of educational environment, reflecting the basic requirements for professional training of future foreign language teachers in higher educational establishment; complex of objective opportunities, which have been purposefully made up and implemented into educational environment, provide solutions to given pedagogical tasks; a set of the following measures increase the efficiency of the process of development of professional potential of future foreign language teachers: information (content of education; cognitive basis of pedagogical process); technological (forms, means, methods, approaches, levels, ways of organization of educational activity; procedural, methodical basis of academic process); personal (behavior, activity, communication, personal qualities of subjects of educational process); psychological (organization of reflective activity, etc.). Taking into consideration the peculiarities of professional activity of future foreign language teachers, the following factors have been singled out as pedagogical conditions that ensure the highest efficiency of development of all components of professional potential of students of investigated specialty: formation of positive "I-conception" of a professional in students' ideology; ensuring the formation of professional outlook of future foreign language teachers by means of expanding the content of academic disciplines with information of interdisciplinary character; use of educational context of professional training of future foreign language teachers as the basis for the development of professional potential; organization of reflective and creative educational activities of students.
Keywords: potential; professional potential; future teachers of foreign language; students; conditions; pedagogical conditions; methods